# Solving a second order ode

Gold Member
I overlooked that one. Does it say there that you are usibg the Frobenius method to solve the Bessel equation ? (other link , link, solution with pictures, a whole chapter, ...).

And you should really start your power series from ##k=0##, not from ##k=-\infty##.

All this with just a little googling and without sitting down and seriously working out your core question ! Lazy me ... My own notes are still somewhere in the attic and also in my brain, but under four and a half decades of dust thats a nice one   , you hit me under the belt lol...i need to upgrade my memory lol

benorin
Homework Helper
Gold Member
Note: Sorry it took so long, been working on this post off and on all day. I just answered your earlier question about the solution to the recurrence relation, and I'm gonnna let you try to figure the rest out...

Given ##y"+\frac {1}{z} y' +\left(\tfrac{z^2-n^2}{z^2}\right) y=0##

Upon setting ##y = \sum_{k=0}^\infty a_{k}z^{k+c}##, we have:

$$\begin{gathered} \left(\tfrac{z^2-n^2}{z^2}\right) y =\left(\tfrac{z^2-n^2}{z^2}\right) \sum_{k=0}^\infty a_{k}z^{k+c} \\ = \sum_{k=0}^\infty a_{k}z^{k+c-2}(z^2 - n^2) \\ \end{gathered}$$

$$\frac {1}{z} y' = \tfrac{1}{z}\sum_{k=0}^\infty (k+c)a_{k}z^{k+c-1} = \sum_{k=0}^\infty (k+c)a_{k}z^{k+c-2}$$

$$y"=\sum_{k=0}^\infty (k+c)(k+c-1)a_kz^{k+c-2}$$

By the given DE, the sum of these three terms vanishes, to wit

$$\begin{gathered} y"+\tfrac{1}{z} y'+\left( \tfrac{z^2-n^2}{z^2}\right) y = 0 \\ \Rightarrow \sum_{k=0}^\infty [ (k+c)(k+c-1) + (k+c) - n^2 ]a_{k}z^{k+c-2}+ \sum_{k=0}^\infty a_{k}z^{k+c} =0 \\ \Rightarrow [c^2-n^2]a_{0}z^{c-2} +[(c+1)^2 -n^2]a_{1}z^{c-1} + \sum_{k=2}^\infty [ (k+c)^2 - n^2 ]a_{k}z^{k+c}+ \sum_{k=0}^\infty a_{k}z^{k+c} =0 \\ \Rightarrow [c^2-n^2]a_{0}z^{c-2} +[(c+1)^2 -n^2]a_{1}z^{c-1} + \sum_{k=0}^\infty \left\{ [ (k+c+2)^2-n^2)]a_{k+2} + a_{k}\right\} z^{k+c} = 0 \\ \end{gathered}$$

All the coefficients of powers of ##z## must vanish, and ##a_0\neq 0\Rightarrow c^2-n^2=0 \Rightarrow c = \pm n ##. Plugging these roots into the next coefficient gives, ##[(\pm n+1) ^2 -n^2]a_1=0\Rightarrow (1\pm 2n)a_1=0## but ##n\in\mathbb{Z}## so ##a_1=0##. Next plug the roots into the ##\text{k}^{th}## coefficient:

$$[ (k\pm n+2)^2-n^2)]a_{k+2} + a_{k}=0\Rightarrow (k\pm n+2+n)(k\pm n+2-n)a_{k+2} = -a_{k}\Rightarrow a_{k+2}=\tfrac{-a_k}{(k+2)(k\pm 2n+2)}$$

From ##a_0\neq 0## and ##a_1=0## this recurrence simplifies to

$$a_{2k+2}=\tfrac{-a_{2k}}{(2k+2)(2k\pm 2n+2)}=\tfrac{-a_{2k}}{4(k+1)(k\pm n+1)}\wedge a_{2k+1}=0\forall k\in\mathbb{N}$$

Let's determine the pattern for ##a_{2k+2}## for small values of ##k## and then try to guess the solution to the recurrence:

$$\boxed{k=0}:\quad a_2=\tfrac{-a_{0}}{4\cdot 1(\pm n+1)}$$

$$\boxed{k=1}:\quad a_4=\tfrac{-a_{2}}{4\cdot 2(\pm n+2)}=\tfrac{(-1)^2 a_{0}}{4^2\cdot 2\cdot 1(\pm n+2)(\pm n+1)}$$

$$\boxed{k=2}:\quad a_6=\tfrac{-a_{4}}{4\cdot 3(\pm n+3)}=\tfrac{(-1)^3 a_{0}}{4^3\cdot 3\cdot 2\cdot 1(\pm n+3)(\pm n+2)(\pm n+1)}$$

My guess:

$$a_{2k+2}=\tfrac{(-1)^{k+1} a_{0}}{4^{k+1}(k+1)! \prod_{j=1}^{k+1}(\pm n+j)}$$

Whelp, my post has got you to this point in the Wikipedia article, I ad-libbed bit along the way to take the easier route, note we've already plugged in the roots, but they differ by an integer so you'll need to read on past that point to see how to derive the other linearly independent solution (after you determine which of the roots solves whichever equation (think it was a DE. Good luck!

• chwala
Gold Member
Note: Sorry it took so long, been working on this post off and on all day. I just answered your earlier question about the solution to the recurrence relation, and I'm gonnna let you try to figure the rest out...

Given ##y"+\frac {1}{z} y' +\left(\tfrac{z^2-n^2}{z^2}\right) y=0##

Upon setting ##y = \sum_{k=0}^\infty a_{k}z^{k+c}##, we have:

$$\begin{gathered} \left(\tfrac{z^2-n^2}{z^2}\right) y =\left(\tfrac{z^2-n^2}{z^2}\right) \sum_{k=0}^\infty a_{k}z^{k+c} \\ = \sum_{k=0}^\infty a_{k}z^{k+c-2}(z^2 - n^2) \\ \end{gathered}$$

$$\frac {1}{z} y' = \tfrac{1}{z}\sum_{k=0}^\infty (k+c)a_{k}z^{k+c-1} = \sum_{k=0}^\infty (k+c)a_{k}z^{k+c-2}$$

$$y"=\sum_{k=0}^\infty (k+c)(k+c-1)a_kz^{k+c-2}$$

By the given DE, the sum of these three terms vanishes, to wit

$$\begin{gathered} y"+\tfrac{1}{z} y'+\left( \tfrac{z^2-n^2}{z^2}\right) y = 0 \\ \Rightarrow \sum_{k=0}^\infty [ (k+c)(k+c-1) + (k+c) - n^2 ]a_{k}z^{k+c-2}+ \sum_{k=0}^\infty a_{k}z^{k+c} =0 \\ \Rightarrow [c^2-n^2]a_{0}z^{c-2} +[(c+1)^2 -n^2]a_{1}z^{c-1} + \sum_{k=2}^\infty [ (k+c)^2 - n^2 ]a_{k}z^{k+c}+ \sum_{k=0}^\infty a_{k}z^{k+c} =0 \\ \Rightarrow [c^2-n^2]a_{0}z^{c-2} +[(c+1)^2 -n^2]a_{1}z^{c-1} + \sum_{k=0}^\infty \left\{ [ (k+c+2)^2-n^2)]a_{k+2} + a_{k}\right\} z^{k+c} = 0 \\ \end{gathered}$$

All the coefficients of powers of ##z## must vanish, and ##a_0\neq 0\Rightarrow c^2-n^2=0 \Rightarrow c = \pm n ##. Plugging these roots into the next coefficient gives, ##[(\pm n+1) ^2 -n^2]a_1=0\Rightarrow (1\pm 2n)a_1=0## but ##n\in\mathbb{Z}## so ##a_1=0##. Next plug the roots into the ##\text{k}^{th}## coefficient:

$$[ (k\pm n+2)^2-n^2)]a_{k+2} + a_{k}=0\Rightarrow (k\pm n+2+n)(k\pm n+2-n)a_{k+2} = -a_{k}\Rightarrow a_{k+2}=\tfrac{-a_k}{(k+2)(k\pm 2n+2)}$$

From ##a_0\neq 0## and ##a_1=0## this recurrence simplifies to

$$a_{2k+2}=\tfrac{-a_{2k}}{(2k+2)(2k\pm 2n+2)}=\tfrac{-a_{2k}}{4(k+1)(k\pm n+1)}\wedge a_{2k+1}=0\forall k\in\mathbb{N}$$

Let's determine the pattern for ##a_{2k+2}## for small values of ##k## and then try to guess the solution to the recurrence:

$$\boxed{k=0}:\quad a_2=\tfrac{-a_{0}}{4\cdot 1(\pm n+1)}$$

$$\boxed{k=1}:\quad a_4=\tfrac{-a_{2}}{4\cdot 2(\pm n+2)}=\tfrac{(-1)^2 a_{0}}{4^2\cdot 2\cdot 1(\pm n+2)(\pm n+1)}$$

$$\boxed{k=2}:\quad a_6=\tfrac{-a_{4}}{4\cdot 3(\pm n+3)}=\tfrac{(-1)^3 a_{0}}{4^3\cdot 3\cdot 2\cdot 1(\pm n+3)(\pm n+2)(\pm n+1)}$$

My guess:

$$a_{2k+2}=\tfrac{(-1)^{k+1} a_{0}}{4^{k+1}(k+1)! \prod_{j=1}^{k+1}(\pm n+j)}$$

Whelp, my post has got you to this point

View attachment 262799

in the Wikipedia article, I ad-libbed bit along the way to take the easier route, note we've already plugged in the roots, but they differ by an integer so you'll need to read on past that point to see how to derive the other linearly independent solution (after you determine which of the roots solves whichever equation (think it was a DE. Good luck!
Thanks for your insight, i know how to work on the rest of the steps leading to the solution....i keep on repeating this statement. My interest was only on how ##a_1=0##, ...only this part...my interest on this question is only and only on that part of the question...

Last edited:
benorin
Homework Helper
Gold Member
All the coefficients of powers of ##z## must vanish, and ##a_0\neq 0\Rightarrow c^2-n^2=0 \Rightarrow c = \pm n ##. Plugging these roots into the next coefficient gives, ##[(\pm n+1) ^2 -n^2]a_1=0\Rightarrow (1\pm 2n)a_1=0## but ##n\in\mathbb{Z}## so ##a_1=0##.
Like it says, because ##1\pm 2n\neq 0\forall n\in\mathbb{N}## hence we must have ##a_1=0## because there is no other way that the coefficient of ##z^{c-1}## can be zero.

Gold Member
yeah yeah and i was able to figure that out in post 25. Thank you sir.

haruspex
Homework Helper
Gold Member
This is the part that i need understanding ...lets assume as you have put it that ##k## starts from ##0→+∞## then how is it that when ##k=1##, that ##a_1=0##
or the other possibility is that my statement (my notes) is/are incorrect.
I still do not understand your question here, and it looks to me that no one else has understood it either, which is why you are not getting a satisfactory answer.
What do you mean "when k=1"? As I wrote in post #23, that is not a 'case'.
I also suggested dropping c, so let's do that. You have ##z^2y''+zy'+y(z^2-n^2)=0## and ##y=\Sigma_{k=0}a_kz^k##.

##z^0: a_0n^2=0##
##z^1: a_1(1-n^2)=0##
##z^k, k>1: a_k(k^2-n^2)+a_{k-2}=0##

From this we get to deduce:
##a_n## can be chosen arbitrarily.
##a_k=0## if either k<n or k+n is odd.
##a_{n+2}=-\frac{a_n}{4n+4}##
Etc.

• chwala
Gold Member
thanks for your asking haruspex, i asked in post 1 on how ##a_1=0##, that was my question, ...and i now know why as shown in my post 25 and also more insight has been given by benorin in post 28. My question has been answered fully sir.

Gold Member
I still do not understand your question here, and it looks to me that no one else has understood it either, which is why you are not getting a satisfactory answer.
What do you mean "when k=1"? As I wrote in post #23, that is not a 'case'.
I also suggested dropping c, so let's do that. You have ##z^2y''+zy'+y(z^2-n^2)=0## and ##y=\Sigma_{k=0}a_kz^k##.

##z^0: a_0n^2=0##
##z^1: a_1(1-n^2)=0##
##z^k, k>1: a_k(k^2-n^2)+a_{k-2}=0##

From this we get to deduce:
##a_n## can be chosen arbitrarily.
##a_k=0## if either k<n or k+n is odd.
##a_{n+2}=-\frac{a_n}{4n+4}##
Etc.

• 